The Implementation of Brainwriting Strategy to Improve Students’ Ability in Writing Recount Text - Handayani, Khani; Toba, Rostanti; Komariah, Anis; Halimah, Nur; Kaharuddin, Nikmala Nemin (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2023)
Writing plays an important role in language acquisition, promoting the students’ experiment to communicate their ideas and strengthen the language ability that they learn in class. However, the researcher found that students had low ability in writing. The research objectives were: (1) To describe the implementation of brainwriting strategy can improve students’ ability in writing recount text. (2) To identify the improvement of students’ ability in writing recount text by using brainwriting strategy. This research used a classroom action research design that conducts in two cycles. The research subject was X IPA 1 grade SMAN 1 Sangatta Selatan students. These research findings showed that: (1) The implementation of the brainwriting strategy where the students divide into some groups that consist of 6 or more participants, then every student write three ideas on the paper until 5 minutes the paper passed to the right person, just like that until all of the participants have got the paper. (2) The improvement of students’ ability to write recount text using brainwriting strategy could be seen from the comparison calculation between the total average cycle I and cycle II scores. The implementation of brainwriting strategy can improve the students’ ability to write recount text.